Correlation between the spinopelvic type and morphological characteristics of lumbar facet joints in degenerative lumbar spondylolisthesis - Leng, Yebo; Tang, Chao; He, Baoqiang; Pu, Xiamin; Kang, Min; Liao, Yehui; Tang, Qiang; Ma, Fei; Wang, Qing; Zhong, Dejun (Journal of neurosurgery. Spine, 2023)
The correlation between the spinopelvic type and morphological characteristics of lumbar facet joints in patients with degenerative lumbar spondylolisthesis (DLS) was investigated. One hundred forty-two patients with L4 DLS were enrolled (DLS group), and 100 patients with lumbar disc herniation without DLS were selected as the control group (i.e., non-lumbar spondylolisthesis [NL] group). Morphological parameters of L4-5 facet joints and L4-5 disc height and angle were measured on 3D reconstructed CT images; namely, the facet joint angle (FJA), pedicle-facet joint angle (PFA), facet joint tropism, and facet joint osteoarthritis (OA). The L4 slip percentage, sacral slope, and lumbar lordosis were measured on radiographs. Patients in the DLS and NL groups were divided into 4 subgroups according to Roussouly classification (types I, II, III, and IV). In the DLS and NL groups, as the spinopelvic type changed from type II to type IV, the facet joint morphology showed a gradual sagittal orientation in the FJA, a gradual horizontal orientation in the PFA, a gradual severity in OA, and a gradual increase in the slip percentage, but changes were completely opposite from type I to type II. Additionally, compared with the NL group, the facet joint morphology in the DLS group had more horizontal orientation in PFA, more sagittal orientation in the FJA, and the facet joint tropism and OA were more severe. Facet joint morphology was correlated with spinopelvic type in the slip segment of DLS. Facet joint morphology was part of the joint configuration in different spinopelvic types, not just the result of joint remodeling after DLS. Moreover, morphological changes of the facet joints and DLS interacted with each other. Additionally, morphological remodeling of the facet joints in DLS played an important role in spinal balance and should be taken into consideration when designing a surgical approach.